Ternary hypervalent silicon hydrides via lithium at high pressure - Liang, Tianxiao (2021)
Hydrogen is rarely observed as a ligand in hypervalent species, however, we find that high-pressure hydrogenation may stabilize hypervalent hydrogen-rich materials. Focusing on ternary silicon hydrides via lithium doping, we find anions composed of hypervalent silicon with H ligands formed under high pressure. Our results reveal two different hypervalent anions: layered SiH5− and tricapped triangular prismatic SiH62−. These differ from octahedral SiH62− described in earlier studies. In addition, there are further hydrogen-rich structures, Li3SiH10 and Li2SiH6+δ, which may be stabilized at high pressure. Our work provides pointers to future investigations on hydrogen-rich materials.